Consistent Use of Assistive Devices for Patient Transfer Is Associated With Less Patient-Initiated Violence: Cross-Sectional Study Among Health Care Workers at General Hospitals. (September 2018) - Pihl-Thingvad, Jesper; Brandt, Lars P. A.; Andersen, Lars L.
This study investigated whether factors related to bodily contact between health care workers and patients were associated with patient-initiated violence. This cross-sectional study surveyed 496 Danish health care workers measuring patient-initiated violence, use of assistive devices, body mass index, physical exertion, frequency of patient transfers, psychosocial work environment, gender, age, and seniority. Associations were modeled using logistic regression analyses using patient-initiated violence as the outcome. Twenty-five percent of the respondents had experienced physical or verbal violence during the past year. Infrequent use of assistive devices, high physical strain, and severe obesity all significantly increased the risk of physical violence (risk ratio [RR] = 1.18, RR = 1.18, and RR = 1.16, respectively), whereas only the lack of assistive device use significantly increased the risk of verbal violence (RR = 1.13 and RR = 1.08). Consistent use of assistive devices appears to reduce the risk of patient-initiated violence. Managers should require the use of assistive devices when designing work processes for patient transfers.